1907 N.J. Laws 116-17, ch. 62, § 2. - (:unkn) unknown (General Publisher, 1907)
For greater certainty it is hereby specified that, in addition to the other powers hereby conferred upon said board, are the following: . . . To regulate and prohibit the use of guns, pistols, firearms and fireworks of all descriptions within the city.
--
Keywords: DISCHARGE